Research on the application of mixed reality technology in the field of art design - Sha Chunfa; Zeng Hanlei; Wu Beibei; Zhang Wenli; Guo Huaquan; Su Wencheng (SHS Web of Conferences, 2022)
Aim: summarize the application of mixed reality technology in the field of art design and analyse its shortcomings and trends. Method: by searching the Web of science as the main source of information to explain the basic concept and development of MR and state of art in product design, display design and interactive design. Discuss the pros and cons of mixed reality technology in human-computer interaction, hardware, and user experience. Result: Mixed reality technology is widely used in art, design, especially in product design, display design, and interactive design. The future trend of mixed reality technology is summarized the combining status of market and industry. Conclusion: The application of mixed reality technology in the field of art design is already drawing more and more attention from industry, but it still lacks enough attention from academia community. This paper systematically introduces the state-of-the-art applications and trends of MR in the field of art design which helps readers to get an insight on this fascinating research area.